Non-coding RNA therapeutics for cardiac regeneration. Issue 3 (26th March 2020) - Braga, Luca; Ali, Hashim; Secco, Ilaria; Giacca, Mauro
Abstract: A growing body of evidence indicates that cardiac regeneration after myocardial infarction can be achieved by stimulating the endogenous capacity of cardiomyocytes (CMs) to replicate. This process is controlled, both positively and negatively, by a large set of non-coding RNAs (ncRNAs). Some of the microRNAs (miRNAs) that can stimulate CM proliferation is expressed in embryonic stem cells and is required to maintain pluripotency (e.g. the miR-302∼367 cluster). Others also govern the proliferation of different cell types, including cancer cells (e.g. the miR-17∼92 cluster). Additional miRNAs were discovered through systematic screenings (e.g. miR-199a-3p and miR-590-3p). Several miRNAs instead suppress CM proliferation and are involved in the withdrawal of CMs from the cell cycle after birth (e.g. the let-7 and miR-15 families). Similar regulatory roles on CM proliferation are also exerted by a few long ncRNAs. This body of information has obvious therapeutic implications, as miRNAs with activator function or short antisense oligonucleotides against inhibitory miRNAs or lncRNAs can be administered to stimulate cardiac regeneration. Expression of miRNAs can be achieved by gene therapy using adeno-associated vectors, which transduce CMs with high efficiency. More effective and safer for therapeutic purposes, small nucleic acid therapeutics can be obtained as chemically modified, synthetic molecules, which can be administered through lipofection or inclusion in lipid or polymer nanoparticles for efficient cardiac delivery. The notion that it is possible to reprogramme CMs into a regenerative state and that this property can be enhanced by ncRNA therapeutics remains exciting, however extensive experimentation in large mammals and rigorous assessment of safety are required to advance towards clinical application.